SEMANTIC ANALYSIS ON METONYMY EXPRESSIONS IN MANADO MALAY - Nurmin Samola; Sjuul Lendo (Universitas Negeri Manado, 2022)
Metonymy according to the Great Dictionary of Indonesian is metonymia which means disclosure in the form of the use of names for other objects that are brands, distinctive features or attributes. The purpose of this study is to describe words or phrases that point to the disclosure of metonymia in Manado Malay as well as explaining the meaning according to the context based on semantic lexial relationships. The data were collected by participatory observation among students majoring in UNIMA English language education. Then the data were analyzed according to the steps of Bogdan and Biklen (1992). The results of the analysis showed that the use of metonymic speech was found in 5 categories based on the theory of Lakoff and Johnson (1980), namely: container for content, part for whole, face for person, place for institution and producer for product. In order not to have misunderstandings in communicating, every speaker must understand the meaning according to the context of the speech